1972
DOI: 10.1063/1.1693984
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Free-Molecule to Continuum Flow in an Annulus

Abstract: Results of precise measurements of the pressure dependence of the flow of gases through annuli of various radius ratio are presented. The data cover a range of Knudsen numbers for about 0.01 to 450. The depth of the Knudsen minimum is found to vary markedly with radius ratio and increases as the radius ratio increases. (Radius ratio is defined as the ratio of inside to outside radii). About 50% of the total change in the depth of the Kundsen minimum occurring between flat plates (radius ratio = 1.0) and capill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…(4), the parameter may take values between 0 and 2, with the upper limit indicating perfect back-reflection. These authors 41,65 (as well as others 25,34 ), found good agreement with experimental data for α > 1, in particular on rough surfaces. However, the values α 2 > 1.4 seen in Table III for Kr, CO 2 , and C 2 H 6 seem rather (and possibly too) high.…”
Section: B Slip and Accommodation Coefficientssupporting
confidence: 69%
“…(4), the parameter may take values between 0 and 2, with the upper limit indicating perfect back-reflection. These authors 41,65 (as well as others 25,34 ), found good agreement with experimental data for α > 1, in particular on rough surfaces. However, the values α 2 > 1.4 seen in Table III for Kr, CO 2 , and C 2 H 6 seem rather (and possibly too) high.…”
Section: B Slip and Accommodation Coefficientssupporting
confidence: 69%
“…Consider flow through a long tube due to an imposed concentration difference An = n0, the concentration at the tube entrance. The free molecule flow in molecules per second may be written as C = y4üAQfmn0 = DfmSfm(n0//i)A (7) where…”
Section: Flow Results and Discussionmentioning
confidence: 99%